A comparison of urban and rural patients with chronic kidney disease referred to Inkosi Albert Luthuli Central Hospital in Durban, South Africa - Singh, Mitesh; Magula, Nombulelo P; Hariparshad, Sudesh; Assounga, Alain GH (African Journal of Nephrology, 2017)
Background: The profiles of patients with chronic kidney disease (CKD) in rural areas have long been thought to differ from those of their urban counterparts. However, there have been few local studies to confirm this. Methods: A retrospective review was conducted to compare the characteristics of patients with CKD from rural and urban areas in the South African province of KwaZulu-Natal that were referred to Inkosi Albert Luthuli Central Hospital (IALCH) from April 2012 to April 2013. Results: A total of 529 patients were included. The mean age of patients from rural areas was lower (40.6 vs. 53.4 years) and all these patients were Black. The rural patients had lower estimated glomerular filtration rates (mean values of 16.3 vs. 25.4 ml/min/1.73 m², p < 0.001). Regarding the prevalence of comorbid conditions, rural patients had higher rates of HIV infection (47.9% vs. 18.3%) but lower rates of hypertension (69.6% vs. 83.9%) and diabetes (20.3% vs. 54.1%). Conclusions: In this study, patients with CKD referred from rural areas differed significantly from those from urban areas. Rural patients presented at a younger age, had a higher prevalence of HIV infection, and had more advanced kidney disease at referral. Poor socio-economic circumstances limiting access to health care and less screening for CKD may contribute to delayed referrals from rural areas.